Concurrent Estimation of Tenofovir, Efavirenz, and Lamivudine in Pure and its Pharmaceutical Dosage Form by Using Novel Validated RP-HPLC Method - Reddy, L. Siva Shankar; Madhuri, D.; Gopal, N. Madana; Raja, J. Kumar; Ravikumar, V.; Himabindu, B.; Rao, R. Nageswara (Pharmaceutical Research: Recent Advances and Trends Vol. 6, 2024)
Aim: This study was designed to develop a reliable method for the estimation of 3TC, TFV, and EFV in pure and its pharmaceutical dosage form by RP-HPLC. Background: An easy, defined, rapid, and accurate reverse-phase high-performance liquid chromatography method was developed and subsequently validated for the concurrent estimation of lamivudine, efavirenz, and tenofovir disoproxil fumarate in their pure blend and combined tablet formulation. Methods: A simple, rapid, accurate, precise, robust, and isocratic reverse-phase high-performance liquid chromatographic (RP-HPLC) method was developed for the estimation of 3TC, TFV, and EFV in a combined dosage form. The method was developed by using Inertsil ODS-3V (250 × 4.6, 5 µm) column, with Mobile phase composition of Acetonitrile: 1% IPA in the ratio of 85:15 at a flow rate of 1 ml/min and the effluents were monitored at 256 nm using PDA detector. Results: 3TC, TFV, and EFV drugs were eluted at retention times of 2.4, 2.8, and 4.5 min (\( ±\) 0.5). The proposed method was validated as per ICH guidelines. The correlation coefficient (R2) was found to be 0.999. All the parameters were found to be within the limits. The recovery studies were carried out and found to be within 98-102% and the %RSD was found to be <2%. The limit of Detection and Limit of Quantification of 3TC, TFV, and EFV were found to be 0.06, 0.09, 0.17 \(μ\)g/ml and 0.18, 0.27, 0.53 \(μ\)g/ml respectively. The results obtained are in good agreement and can be used for the routine analysis of drugs in combined dosage form in laboratories and for Quality control purposes. Conclusion: The present method was developed and validated using 1% IPA: ACN. IPA enhances the selectivity of binary or tertiary mixtures. The main reason for the use of IPA as a part of the aqueous mobile phase is to keep the column free of undesired adsorbed contaminants from the sample or a sample matrix. This may change the retention behaviour of the analyte or as a baseline noise or drift. By using IPA which acts as a good washing agent of the column when compared to other solvents. The proposed method has a shorter analysis time, which allows it to be applied to several samples in less time. As a result, the proposed method was discovered to be unique, simple, accurate, and resilient, and validation experiments revealed that the proposed methods are adequate for routine quality analysis of the combination dosage form.